Probiotics and prebiotics in pediatrics: where are we now? - Szajewska, Hania (The Turkish Journal of Pediatrics, 2007)
In recent years, probiotics and prebiotics have become a hot topic. There are an increasing number of health benefits attributed to them. However, only a few of the benefits have been confirmed in well-conducted randomized controlled trials. This paper was written to evaluate the evidence on the effect of administration of probiotics and prebiotics in children. Electronic databases and the reference lists of publications were searched for randomized controlled trials or their meta-analyses (all up until April 2007). Based on the available evidence, to date, the most extensively studied application and the best documented is the use of some probiotic strains for the treatment of acute infectious diarrhea and prevention of antibiotic-associated diarrhea. Many other benefits, both of probiotics and prebiotics, are largely unproven, but there is a growing body of scientific evidence in support of such benefits. Guidance is needed as to which agent to use, timing, dosage and mode of administration.